Generalized Correlations for Characteristic Variables and Thermophysical Properties of Osmotically Dehydrated Fruits - Rodriguez, Anabel (2012)
Based on experiments on osmotic dehydration of different fruits, with diverse dehydrating solutions and working conditions, and on an extensive search of the literature on osmotic dehydration, general linear correlations between water content (WC) and soluble solids (SS) content of fruits dehydrated in sugar or alcohol solutions have been developed for each type of fruit that allows characterization of both properties with only one rapid determination of either property. A linear regression for SS vs. WC including all of the experimental data for the seven types of fruits tested (apple, strawberry, pear, kiwi, plum, nectarine, and melon) and the five solutes used in those experiments (sucrose, glucose, xylitol, sorbitol, polyethylene glycol) was obtained with a high regression coefficient.Based on experimental data determined in this work in the range -40 to 40°C, correlations are established between heat capacity and enthalpy with water content and temperature for both fresh strawberries and strawberries that were osmotically dehydrated in different solutions. In addition, general polynomial correlations for the initial freezing temperature of fresh and osmotically dehydrated fruits as a function of water content and type of dehydrating solute are proposed.